Improved Immune Responses in Young and Aged Mice with Adjuvanted Vaccines against H1N1 Influenza Infection - Baldwin, Susan L.; Hsu, Fan-Chi; Van Hoeven, Neal; Gage, Emily; Granger, Brian; Guderian, Jeffrey A.; Larsen, Sasha E.; Lorenzo, Erica C.; Haynes, Laura; Reed, Steven G.; Coler, Rhea N. (Frontiers in Immunology, 2018)
Elderly people are at high risk for influenza-related morbidity and mortality due to progressive immunosenescence. While toll-like receptor (TLR) agonist containing adjuvants, and other adjuvants, have been shown to enhance influenza vaccine-induced protective responses, the mechanisms underlying how these adjuvanted vaccines could benefit the elderly remain elusive. Here we show that a split H1N1 influenza vaccine (sH1N1) combined with a TLR4 agonist, glucopyranosyl lipid adjuvant formulated in a stable oil-in-water emulsion (GLA-SE), boosts IgG2c:IgG1 ratios, enhances hemagglutination inhibition (HAI) titers, and increases protection in aged mice. We find that all adjuvanted sH1N1 vaccines tested were able to protect both young and aged mice from lethal A/H1N1/California/4/2009 virus challenge after two immunizations compared to vaccine alone. We show that GLA-SE combined with sH1N1, however, also provides enhanced protection from morbidity in aged mice given one immunization (based on change in weight percentage). While the GLA-SE-adjuvanted sH1N1 vaccine promotes the generation of cytokine-producing T helper 1 (Th1) cells, germinal center (GC) B cells and long-lived bone marrow plasma cells (BMPCs) in young mice, these responses were muted in aged mice. Differential in vitro responses, dependent on age, were also observed from mouse-derived bone marrow dendritic cells (BMDCs) and lung homogenates following stimulation with adjuvants, including GLA-SE. Besides enhanced HAI titers, additional protective factors elicited with sH1N1+GLA-SE in young mice were observed, including (a) rapid reduction of viral titers in the lung, (b) prevention of excessive lung inflammation, and (c) homeostatic maintenance of alveolar macrophages (AMs) following H1N1 infection. Collectively, our results provide insight into mechanisms of adjuvant-mediated immune protection in the young and elderly.